2016
DOI: 10.1111/jan.12954
|View full text |Cite
|
Sign up to set email alerts
|

Substitution of general practitioners by nurse practitioners in out‐of‐hours primary care: a quasi‐experimental study

Abstract: Aim. To provide insight into the impact of substituting general practitioners with nurse practitioners in out-of-hours services on: (1) the number of patients; and (2) general practitioners' caseload (patient characteristics, urgency levels, types of complaints). Background. General practitioners' workload during out-of-hours care is high, and the number of hours they work out-of-hours has increased, which raises concerns about maintaining quality of care. One response to these challenges is shifting care to n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
27
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 54 publications
0
27
1
Order By: Relevance
“…However, contrary to some of the evidence (Horrocks et al, 2002), ANP consultations were not longer, the median length of home visits being the same for ANPs and GPs. Unlike in the studies by Edwards et al (2009) and Van der Biezen et al (2016), no distinction was found between the ANP and the GP attending to differing grades of patient acuity or patient condition. Prescribing patterns were also very similar, although the ANPs prescribed more analgesics than the GPs.…”
Section: Discussioncontrasting
confidence: 63%
See 2 more Smart Citations
“…However, contrary to some of the evidence (Horrocks et al, 2002), ANP consultations were not longer, the median length of home visits being the same for ANPs and GPs. Unlike in the studies by Edwards et al (2009) and Van der Biezen et al (2016), no distinction was found between the ANP and the GP attending to differing grades of patient acuity or patient condition. Prescribing patterns were also very similar, although the ANPs prescribed more analgesics than the GPs.…”
Section: Discussioncontrasting
confidence: 63%
“…One of the GP team was replaced by a NP, providing acute care during daytime weekend hours, compared to the control group of GPs only. The results showed that NPs can make a valuable contribution to patient care in the OOH (Van der Biezen et al, 2016). The number of patients seen was similar between the two study groups; however, the case mix was very different between the NP and the GPs, with GPs treating more older patients and higher urgency levels.…”
Section: Liter Ature Re Vie Wmentioning
confidence: 90%
See 1 more Smart Citation
“…Positive outcomes are reported in the literature, both in daytime general practices and at GPCs, in terms of physicians’ workload, patients’ experiences, and care outcomes [21]. A study at one GPC showed that nurses can adequately deal with 77% of all consultations [22], but further studies on this subject are recommendable.…”
Section: Discussionmentioning
confidence: 99%
“…This gave a more detailed picture of their daily practices, and allowed for continuous monitoring. A similar method of measuring autonomy was used in a study by van der Biezen et al(33).ResultsNumber of NP consultations and share of home visitsOver the whole data collection period, the NP of Practice A had 1247 consultations. The mean number of consultations per month was 96 (SD 47.9).…”
mentioning
confidence: 99%